Development and Creation of Software and Information Environment for Simulation of Nuclear Facility; Computation, Automation, Information Technologies and Safety Systems in Nuclear Industry; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Godovykh A. V. Aleksey Valeryevich (Radiation Technologies in Medicine, 2015)
Title screen